2018
DOI: 10.1016/j.jinorgbio.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of water soluble arene Ru(II) enantiomers with amino-oxime ligands

Abstract: New water soluble, enantiopure arene ruthenium compound SS-(1R,4S)-[(η-p-cymene)Ru{ĸNH(Bn),ĸNOH}Cl]Cl (Bn = benzyl, 1a') has been synthesized. The novel compound along with that previously described RR-(1S,4R)-[(η-p-cymene)Ru{ĸNH(Bn),ĸNOH}Cl]Cl (1a) was evaluated by polarimetry, ultra-violet and circular dichroism spectroscopy. The structure of novel ruthenium derivative 1a' was determined by single crystal X-ray crystallography. Both enantiomers have been tested against several cancer cell lines in vitro: pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 107 publications
0
10
0
1
Order By: Relevance
“…It can be pointed out that the observed IC 50 values, ranging from 1.72 to 5.82 μM, are comparable to data reported in the literature for various types of piano-stool ruthenium­(II) complexes. However, it can be stressed that the IC 50 values for 3 Cl iPr , 3 I iPr and 3 dmso iPr , given in Table , were determined after 24 h of incubation with cells, whereas most of the IC 50 values found in the literature were obtained after a drug-exposure time of 48, 72, or 96 h; hence, the low-micromolar IC 50 values achieved after 24 h of incubation with 3 CI iPr , 3 I iPr , and 3 dmso iPr indicate that they are highly cytotoxic. Notable activities after 24 h of incubation have been described for tethered, acylpyrazolonato-containing, or amino-oxime-based half-sandwich ruthenium­(II) complexes, but 3 Cl iPr , 3 I iPr , and 3 iPr dmso are comparatively more efficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be pointed out that the observed IC 50 values, ranging from 1.72 to 5.82 μM, are comparable to data reported in the literature for various types of piano-stool ruthenium­(II) complexes. However, it can be stressed that the IC 50 values for 3 Cl iPr , 3 I iPr and 3 dmso iPr , given in Table , were determined after 24 h of incubation with cells, whereas most of the IC 50 values found in the literature were obtained after a drug-exposure time of 48, 72, or 96 h; hence, the low-micromolar IC 50 values achieved after 24 h of incubation with 3 CI iPr , 3 I iPr , and 3 dmso iPr indicate that they are highly cytotoxic. Notable activities after 24 h of incubation have been described for tethered, acylpyrazolonato-containing, or amino-oxime-based half-sandwich ruthenium­(II) complexes, but 3 Cl iPr , 3 I iPr , and 3 iPr dmso are comparatively more efficient.…”
Section: Resultsmentioning
confidence: 99%
“…IC 50 values were then determined for compounds 3 Cl indicate that they are highly cytotoxic. Notable activities after 24 h of incubation have been described for tethered, 69 acylpyrazolonato-containing, 70 or amino-oxime-based halfsandwich ruthenium(II) complexes, 71 Dimethyl(1-pyrenyl)phosphane versus Diisopropyl-(1-pyrenyl)phosphane. As mentioned in the Introduction, the use of the new ligand diisopropyl(1-pyrenyl)phosphane (L) originates from previous studies, which have shown that Pligands of the type PR 1 R 2 (1-pyrenyl), which give rise to [RuX 2 (η 6 -arene)(PR 1 R 2 (1-pyrenyl))] compounds, exhibit remarkable cytotoxic properties; in particular, the chlorido Ru complex with the ligand dimethyl(1-pyrenyl)phosphane and η 6 -methyl benzoate, namely [RuCl 2 (η 6 -methyl benzoate)-(dimethyl(1-pyrenyl)phosphane)], exhibited IC 50 values in the low micromolar range for various cancer cell lines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cuvea-Alique and co-workers [67] evaluated the anticancer activities of arene Ru(II) enantiomers witzzh aminooxime ligands-Figure 10. The oxime-containing Ru(II) compounds have shown potent anticancer activities against a broad range of different cancer cell lines, with no significant differences between the two enantiomers.…”
Section: Chiral Ruthenium Anticancer Complexesmentioning
confidence: 99%
“…IC 50 değerindeki düşüş sitotoksik aktivitedeki artışı göstermektedir. Kompleks (2a), her üç uygulama zamanı için de günümüzde hali hazırda kullanılan kemoterapötik bir ajan olan cisplatinden daha yüksek sitotoksik aktivite göstermiştir [18][19][20] . Kompleksin (2a), PC-3 insan prostat kanser hücrelerinde 24, 48 ve 72 saat için elde edilen IC 50 değerleri WI-38 insan sağlıklı akciğer fibroblast hücreleri için elde edilen IC 50 değerinden daha küçüktür.…”
Section: Bulgularunclassified